Study The Influence of The Number of Beams on Radiotherapy Plans for The Hyopfractionated Treatment of Breast Cancer Using Biological Model - Mansour, Z.; M. Attalla, Ehab; Sarhan, A.; Awad , Ibrahim A.; Abdel Hamid, M.I. (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Purpose: To evaluate the biologic differences in treatment plans with different number of beams on 3D conformal radiotherapy for breast cancer patients, and compute the percent of probability to tumor control and complication of normal tissue probability using matlap program. Then determine the optimum plan through these values.